Measuring intangible asset: firm reputation - Edi, Edi; Wati, Erna (Business: Theory and Practice, 2022)
The purpose of this research is to find out the measurement of firm reputation that are still relevant to represent firm reputation. The measurement that are being tested in this research are CSR Award, Firm Age, Listing Age, Market Capitalization, Buy and Hold Abnormal Return and Price Earnings Ratio as the measurement for firm reputation. The novelty of this research is able to prove LQ45 are able to become a measurement to represent firm reputation. The data sample of this research are companies that listed in Indonesia stock exchange between 2016 till 2020. To select the research sample,this research conducted purposive sampling. This research data analysis is using SPSS program to conduct descriptive statistical test and spearman correlation test to measure the correlation between each variable. The results of this study show that measurement like listing age and BHAR are no longer a relevant measurement to measure firm reputation but CSR Award, Firm Age, Market Capitalization and Price earning Ratio are still a relevant measurement to measure firm reputation.This research also found that LQ45 can be used as the novel measurement for firm reputation. This research results will be helpful for researcher in firm reputation area.